Plasma concentrations of lipoproteins and risk of lower-limb peripheral artery disease in people with type 2 diabetes: the SURDIAGENE study - Bertrand, Capucine; Saulnier, Pierre-Jean; Potier, Louis; Croyal, Mikaël; Blanchard, Valentin; Gand, Elise; Ragot, Stéphanie; Schneider, Fabrice; Bocock, Olivia; Baillet-Blanco, Laurence; Velho, Gilberto; Marre, Michel; et al. (Diabetologia, 2021)
Aims/hypothesis The lipid profile has not been fully investigated in individuals with peripheral artery disease (PAD). We aimed to evaluate the relationship between plasma concentrations of lipoproteins and the prevalence of lower-limb PAD at baseline and its incidence during follow-up in people with type 2 diabetes. Methods Plasma concentrations of total cholesterol, HDL-cholesterol, triacylglycerol and apolipoprotein (Apo) A-I, ApoA-II, ApoB-100 and Apo(a) were measured at baseline using colorimetric or MS methods in the SURDIAGENE cohort. Total cholesterol/HDL-cholesterol ratio, non-HDL-cholesterol and LDL-cholesterol were estimated using computation formulas. Logistic and Cox proportional hazard regression models were fitted to estimate OR or HR, with related 95% CI, for baseline prevalence or incidence of major PAD (lower-limb amputation or requirement of revascularisation) during follow-up by increasing lipoprotein tertiles, after adjustment for key confounders. Results Among 1468 participants (women 42%, mean ± SD age 65 ± 11 years, duration of diabetes 14 ± 10 years at baseline), 129 (8.8%) had a baseline history of major PAD. Major PAD was less prevalent at baseline in the highest (vs lowest) tertile of HDL-cholesterol (OR 0.42 [95% CI 0.26, 0.71], p = 0.001) and ApoA-I (OR 0.39 [95% CI 0.23, 0.67], p = 0.0007), and more frequent in the highest tertile of total cholesterol/HDL-cholesterol ratio (OR 1.95 [95% CI 1.18, 3.24], p = 0.01). Among 1339 participants without a history of PAD at baseline, incident PAD occurred in 97 (7.2%) during a median (25th–75th percentile) duration of follow-up of 7.1 (4.4–10.7) years, corresponding to 9685 person-years and an incidence rate of 9.8 (95% CI 8.0, 12.0) per 1000 person-years. The risk of incident PAD was lower in the top (vs bottom) tertile of HDL-cholesterol (HR 0.54 [95% CI 0.30, 0.95], p = 0.03) or ApoA-I (HR 0.50 [95% CI 0.28, 0.86], p = 0.01) and higher in the top tertile of total cholesterol/HDL-cholesterol ratio (HR 2.81 [95% CI 1.61, 5.04], p = 0.0002) and non-HDL-cholesterol (HR 1.80 [95% CI 1.06, 3.12], p = 0.03). Conclusions/interpretation We reported independent associations between HDL-cholesterol, ApoA-I, total cholesterol/HDL-cholesterol ratio or non-HDL-cholesterol and the prevalence or the incidence of major PAD in people with type 2 diabetes. Our findings provide a picture of lipoprotein profile in people with type 2 diabetes. Graphical abstract